2021
DOI: 10.1007/s00186-021-00747-9
|View full text |Cite
|
Sign up to set email alerts
|

Chance-constrained games with mixture distributions

Abstract: In this paper, we consider an n-player non-cooperative game where the random payoff function of each player is defined by its expected value and her strategy set is defined by a joint chance constraint. The random constraint vectors are independent. We consider the case when the probability distribution of each random constraint vector belongs to a subset of elliptical distributions as well as the case when it is a finite mixture of the probability distributions from the subset. We propose a convex reformulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…In this paper, we extend the results of [19,20] to the general case where the payoff function is random and the strategy profile set of each player is defined by elliptically distributed dependent joint chance constraints. We derive a new reformulation of joint chance constraint with dependent random constraint vectors and show that there exists a Nash equilibrium of the game under mild conditions on the payoff functions.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…In this paper, we extend the results of [19,20] to the general case where the payoff function is random and the strategy profile set of each player is defined by elliptically distributed dependent joint chance constraints. We derive a new reformulation of joint chance constraint with dependent random constraint vectors and show that there exists a Nash equilibrium of the game under mild conditions on the payoff functions.…”
Section: Introductionmentioning
confidence: 88%
“…However, the strategy sets containing chance constraints are often considered in various applications, e.g., risk constraints in portfolio optimization problem [11] and resource constraints in stochastic shortest path problem [4]. Recently, the games with chance constraint based strategy sets are introduced in the literature [18,19,20,26,27]. Singh and Lisser [26] considered a 2-player zero-sum game with individual chance constraints and showed that a saddle point equilibrium problem is equivalent to a primaldual pair of second order cone programs when the random constraint vectors follow elliptically symmetric distribution.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations